Alma-Tadema et le détournement de la culture savante - Anne-Florence Gillard-Estrada (Cahiers Victoriens et Edouardiens)
Alma-Tadema’s recreations of Antiquity were informed by his vast archaeological and literary knowledge of Roman and Greek culture, but at the same time, he dealt with themes that were easily readable by middle-class or popular publics. This paper aims at showing that there are different readings of his painting that inscribe him both in the “commodity culture” of the age—because of his interest for objects and archaeological artefacts that are reproduced time and again in his canvases—and in the Aesthetic Movement that posited the doctrine of art for art’s sake. Alma-Tadema also resorted to erudition in order to offer a subversive vision of Antiquity centred on objects. The painter thus expressed the “repressed” of Victorian society—such as unorthodox forms of sexuality or dionysiac practices—thanks to the reutilisation of antique artefacts.